Determination and Combination of Monthly Gravity Field Time Series from Kinematic Orbits of GRACE, GRACE-FO and Swarm - Grombein, Thomas; Lasser, Martin; Arnold, Daniel; Meyer, Ulrich; Jäggi, Adrian (Springer International Publishing, 2022)
Abstract Dedicated gravity field missions like GRACE and GRACE-FO use ultra-precise inter-satellite ranging observations to derive time series of monthly gravity field solutions. In addition, any (non-dedicated) Low Earth Orbiting (LEO) satellite with a dual-frequency GNSS receiver may also serve as a gravity field sensor. To this end, GPS-derived kinematic LEO orbit positions are used as pseudo-observations for gravity field recovery. Although less sensitive, this technique can provide valuable information for the monitoring of large-scale time-variable gravity signals, particularly for those months where no inter-satellite ranging measurements are available. Due to a growing number of LEO satellites that collect continuous and mostly uninterrupted GPS data, the value of a combined multi-LEO gravity field time series is likely to increase in the near future. In this paper, we present monthly gravity field time series derived from GPS-based kinematic orbit positions of the GRACE, GRACE-FO and Swarm missions. We analyze their individual contribution as well as the additional benefit of their combination. For this purpose, two combination strategies at solution level are studied that are based on (i) least-squares variance component estimation, and (ii) stochastic properties of the gravity field solutions. By evaluating mass variations in Greenland and the Amazon river basin, the resulting gravity field time series are assessed with respect to superior solutions based on inter-satellite ranging.